Impact of Talent Management on Organizational Performance and Affective Commitment: Mediating Role of Competency Development among University Teachers - Noor, Sumaya; Malik, Najma Iqbal; Atta, Mohsin (The journal of contemporary issues in business and government, 2022)
The present study investigates the outcomes of talent management among university teachersalong with the role of competency development as a mediator. The design of the study was correlational.The study sample consisted of 190teachers. The sample was further divided into males (n = 94) and females (n = 96) by using the purposive sampling technique. The age of the sample was ranged from 25 to 60 years. English versions of talent management, organizational performance, affective commitment, and competency development were used in the study to assess variables. Pearson correlation indicated that all variables are positively correlated. Multiple regression analysis indicated that subscales of talent managementwere positive predictors ofaffective commitment and performance. Competency development shows mediation betweensubscales of talent management and outcomes (i.e., organizational performance and affective commitment). Male scored high on rewarding (subscale). The implications, limitations and recommendations for the future were discussed.